Optimal monetary policy and firm entry - Vivien Lewis (National Bank of Belgium, 2009)
This paper describes optimal monetary policy in an economy with monopolistic competition, endogenous firm entry, a cash-in-advance constraint and pre-set wages. Firms must make profits in order to cover entry costs; thus a mark-up on goods prices is necessary. Without this mark-up, profits would be zero and no firm would enter the market, resulting in zero production. Therefore, the mark-up should not be removed. In this economy with market entrants, goods are more expensive than in a competitive economy with marginal cost pricing. This leads to a misallocation of resources, because leisure is not sold at a mark-up. Goods and leisure are two sources of utility that households trade off against each other. Thus, they may buy too much leisure instead of consumption goods. The consequence is that labour supply and production are sub-optimally low. Due to the labour requirement at market entry stage, insufficient labour supply also implies too little entry and too few firms in equilibrium. In the absence of fiscal instruments such as labour income subsidies, the optimal monetary policy under sticky wages achieves higher welfare than under flexible wages. The policy-maker uses the money supply instrument to raise the real wage - the cost of leisure - above its flexible-wage level, in response to expansionary shocks. This induces a rise in labour supply, more production of goods and more new firms
Keywords: E52; E63; 330; entry; optimal policy; Geldpolitik; Markteintritt; Mark-up Pricing; Geldmengensteuerung; Erwerbstätigkeit; Theorie